Two-dimensional correlation spectroscopy in polymer study - Park, Yeonju; Noda, Isao; Jung, Young Mee (Frontiers in Chemistry, 2015)
This review outlines the recent works of two-dimensional correlation spectroscopy (2DCOS) in polymer study. 2DCOS is a powerful technique applicable to the in-depth analysis of various spectral data of polymers obtained under some type of perturbation. The powerful utility of 2DCOS combined with various analytical techniques in polymer studies and noteworthy developments of 2DCOS used in this field are also highlighted.